Antigen Cross-Presentation by Macrophages - Muntjewerff, Elke M.; Meesters, Luca D.; van den Bogaart, Geert (Frontiers in Immunology, 2020)
The contribution of dendritic cell (DC) antigen cross-presentation to the activation of CD8+ T lymphocytes for immune defense against tumors, viruses and intracellular pathogens has been recognized widely. Although originally thought to be an exclusive characteristic of DCs, recently also other immune cells, particularly macrophages, have been shown capable of cross-presentation. Here we provide an overview of in vitro and in vivo evidence on cross-presentation by macrophages. As we discuss, it is now firmly established that various types of tissue-resident macrophages are able to cross-present via similar cellular pathways as DCs. This is based on a wide range of antigens in macrophages from many different tissue origins such as blood, tumors and lymphoid tissue. However, the physiological relevance of macrophage cross-presentation with potential contributions to activation of CD8+ T lymphocytes is still mostly unknown. While cross-presentation by various types of pro-inflammatory macrophages might be involved in cross-priming of naive CD8+ T lymphocytes, it might also be involved in local re-activation of memory and/or effector CD8+ T lymphocytes. Moreover, cross-presentation by anti-inflammatory macrophages could be related to immune tolerance. Since cross-presentation promotes the initiation and potentiation of antigen-specific CD8+ T lymphocyte responses, stimulating macrophages to cross-present antigen might be a promising strategy for anti-tumor or anti-viral therapies.